2023
DOI: 10.3389/fonc.2023.993540
|View full text |Cite
|
Sign up to set email alerts
|

The road to breast cancer screening with diffusion MRI

Abstract: Breast cancer is the leading cause of cancer in women with a huge medical, social and economic impact. Mammography (MMG) has been the gold standard method until now because it is relatively inexpensive and widely available. However, MMG suffers from certain limitations, such as exposure to X-rays and difficulty of interpretation in dense breasts. Among other imaging methods, MRI has clearly the highest sensitivity and specificity, and breast MRI is the gold standard for the investigation and management of susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 112 publications
0
1
0
Order By: Relevance
“…CF-related lung disease can make it difficult for patients to undergo mammography due to positioning and breathing difficulties. In such cases, alternative imaging modalities such as breast ultrasound or magnetic resonance imaging (MRI) may be considered [88]. Collaborating with healthcare providers experienced in managing breast cancer screening in individuals with CF can help develop appropriate and effective screening strategies.…”
Section: Breast Cancermentioning
confidence: 99%
“…CF-related lung disease can make it difficult for patients to undergo mammography due to positioning and breathing difficulties. In such cases, alternative imaging modalities such as breast ultrasound or magnetic resonance imaging (MRI) may be considered [88]. Collaborating with healthcare providers experienced in managing breast cancer screening in individuals with CF can help develop appropriate and effective screening strategies.…”
Section: Breast Cancermentioning
confidence: 99%
“…Also, the experimental results that were reported by Fu et al ( 19 ) indicated that magnetic resonance imaging (MRI) is worthy of clinical promotion and usage, based on its ability to diagnose the ALN metastasis of BC. However, MRI was limited by factors such as high sensitivity and costs, low specificity, and the long time for preliminary diagnosis ( 20 ), so its diagnostic value was not discussed in this study. Therefore, an NSLNM risk prediction model based on the Chinese population needs to be developed to further guide clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…While forthcoming prospective studies may present difficulties in comparisons due to a lack of reference standards, they are anticipated to demonstrate superior efficacy. Additionally, using DLSR on data with higher acquired spatial resolution by maintaining current scan durations, there is potential to detect smaller, early‐stage breast cancers with greater accuracy, thereby potentially reestablishing DWI as a more reliable screening tool 7 . This anticipated shift could significantly fortify the array of non‐invasive diagnostic approaches in the battle against breast cancer, leveraging the inherent capabilities of DWI in clinical application.…”
mentioning
confidence: 99%